Peningkatan Budaya Wirausaha Pemuda Berbasis Produk Kopi Wilis sebagai Pendukung Pariwisata di Danau Ngebel, Kabupaten Ponorogo, Jawa Timur - Saputra, Anggara Wiyono Wit; Sugiarto, Sugiarto; Widhiyanuriyawan, Denny; Setyono, Langgeng (Universitas Nusantara PGRI Kediri, 2024)
The Ngebel area in Ponorogo Regency, East Java, is one of the hidden tourist destinations that has yet to be fully exposed but is becoming a favorite tourist destination in Indonesia. The natural beauty of Lake Ngebel, in the form of a natural lake, is an attraction in itself that can be explored and developed as a natural tourist area in Indonesia. Apart from the natural lake, which holds potential, the Ngebel area is also known for its potential as a robusta coffee center, famously known as Wilis coffee. This initiative aims to provide mentoring and technology application to the youth in Ngebel village and its surrounding areas to become a driving force for the emergence of young entrepreneurs in building businesses based on local commodities, especially Wilis coffee products, thus making it a flagship product and supporting the development of Lake Ngebel tourism. The community service activities consist of entrepreneurial training, the application of appropriate technology such as coffee roasting machine production, and mentoring millennial café entrepreneurs in the Lake Ngebel area as a tourist destination. The results of these activities show that the application of appropriate technology in roasting coffee with various flavors increases the entrepreneurial spirit of the youth in the Lake Ngebel area and can be utilized to better market Wilis coffee products, thereby supporting tourism activities in the Lake Ngebel area.